A Randomized, Double-Blind, Placebo-Controlled, Phase 2b Study to Evaluate the Safety and Efficacy of Recombinant Human Soluble Thrombomodulin, ART-123, in Patients With Sepsis and Suspected Disseminated Intravascular Coagulation* - Vincent JL. (2014)
UNASSIGNED : To determine the safety and efficacy of recombinant thrombomodulin (ART-123) in patients with suspected sepsis-associated disseminated intravascular coagulation. UNASSIGNED : Phase 2b, international, multicenter, double-blind, randomized, placebo-controlled, parallel group, screening trial. UNASSIGNED : Two hundred and thirty-three ICUs in 17 countries. UNASSIGNED : All adult patients admitted with sepsis and suspected disseminated intravascular coagulation as assessed using a modified International Society on Thrombosis and Hemostasis score. UNASSIGNED : Patients were randomized to receive IV ART-123 (0.06 mg/kg/d) for 6 days or placebo, in addition to standard of care. The primary endpoint was reduction in mortality. Secondary endpoints included reversal of overt disseminated intravascular coagulation and reduction in disease severity. UNASSIGNED : A total of 750 patients were randomized, nine of whom did not receive the allocated treatment so that 371 patients received ART-123 and 370 received placebo. There were no meaningful differences between the two groups in any of the baseline variables. Twenty-eight-day mortality was 17.8% in the ART-123 group and 21.6% in the placebo group (Cochran-Mantel-Haenszel two-sided p value of 0.273 in favor of ART-123, which met the predefined statistical test for evidence suggestive of efficacy). There were no statistically significant differences in event-free and alive days between the two groups. d-dimer, prothrombin fragment F1.2 and TATc concentrations were lower in the ART-123 group than in the placebo group. There were no differences between the two groups in organ function, inflammatory markers, bleeding or thrombotic events or in the development of new infections. In post hoc analyses, greatest benefit from ART-123 was seen in patients with at least one organ system dysfunction and an international normalized ratio greater than 1.4 at baseline. UNASSIGNED : ART-123 is a safe intervention in critically ill patients with sepsis and suspected disseminated intravascular coagulation. The study provided evidence suggestive of efficacy supporting further development of this drug in sepsis-associated coagulopathy including disseminated intravascular coagulation. Future study should focus on using ART-123 in the subgroup of patients most likely to respond to this agent.